Assessing I-HappySchool: A Mobile-Based Instrument to Support Parental Participation in Child-Friendly School Assessment - Sobri, Ahmad Yusuf; Yafie, Evania (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Despite the increasing global emphasis on child-friendly school (CFS) frameworks, parental participation in formal CFS assessment processes remains limited and often informal. This study developed I-HappySchool, a mobile-based instrument designed to facilitate structured parental engagement in assessing child-friendly school practices. A mixed-methods design was employed, integrating an ADDIE-based research and development model with a quasi-experimental nonequivalent-groups pretest–posttest design. The study was conducted in urban kindergartens in East Java, Indonesia, involving twenty parents or guardians from both public and private institutions. Data were collected through questionnaires, observation checklists, and expert validation forms. Quantitative data were analysed using descriptive statistics and independent-samples t-tests, while qualitative data were examined thematically to capture patterns of implementation across learning contexts. Expert evaluation indicated strong feasibility of the instrument, achieving an overall validity score of 87%. Post-intervention findings revealed comparable levels of CFS implementation in public and private settings across classroom and outdoor learning environments (p > 0.05). Among the assessed dimensions, effectiveness, health and safety, and gender sensitivity showed relatively higher performance, whereas democratic participation and equitable access remained comparatively weaker, with several indicators scoring below 60%. These findings suggest that a validated mobile-based instrument can support more systematic CFS assessment and enhance structured parental participation in early childhood education. Nevertheless, the findings should be interpreted cautiously due to the limited sample size and short implementation period.